Analisis Pertumbuhan Penjualan, Ukuran Perusahaan, Leverage dan Capital Intensity Terhadap Profitabilitas PT Mandala Multifinance - Shaquila Farah Aprila; Nor Norisanti; Faizal Mulia Z (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of sales growth, company size, leverage and capital intensity on profitability. The research method used in this research is quantitative research method with associative descriptive approach. The sample technique used by analysing the company's financial statements for the last few years and the data analysis technique is Regression with the help of SPSS 26 software. The results of this study indicate that PT Mandala Finance, Tbk has successfully built sales growth, company size, leverage, capital intensity and profitability in these decades. Sales growth shows that it has a positive significance value, which means that sales growth has a positive and significant effect on profitability. Company size has no significant effect on profitability. Leverage has a negative significant effect on profitability. Capital intensity has no significant effect on profitability. PT Mandala needs to make strategy adjustments to maintain stable sales growth, manage leverage wisely, and maximise the use of fixed assets in order to maintain optimal profitability. The integration of theory and previous research findings confirms that sustainable growth requires a balance between asset expansion, debt management, and efficient use of capital.